Sex differences in cannabis withdrawal symptoms among treatment-seeking cannabis users - Herrmann, Evan S. (Exp Clin Psychopharmacol, 2015)
Over 300,000 individuals enter treatment for cannabis use disorders (CUDs) in the U.S. annually. Cannabis withdrawal is associated with poor CUD treatment outcomes, but no prior studies have examined sex differences in withdrawal among treatment-seeking cannabis users. Treatment-seeking cannabis users (45 women and 91 men) completed a Marijuana Withdrawal Checklist (MWC) at treatment intake to retrospectively characterize withdrawal symptoms experienced during their most recent quit attempt. Composite Withdrawal Discomfort Scale (WDS) scores were calculated using the 14 items on the MWC that correspond to valid cannabis withdrawal symptoms described in DSM-5. Demographic and substance use characteristics, overall WDS scores, and scores on individual WDS symptoms were compared between women and men. Women had higher overall WDS scores than men, and women had higher scores than men on six individual symptoms in two domains, mood symptoms (irritability, restlessness, increased anger, violent outbursts) and gastrointestinal symptoms (nausea, stomach pain). Follow-up analyses isolating the incidence and severity of WDS symptoms demonstrated that women generally reported a higher number of individual withdrawal symptoms than men, and that they reported experiencing some symptoms as more severe. This is the first report to demonstrate that women seeking treatment for CUDs may experience more withdrawal then men during quit attempts. Prospective studies of sex differences in cannabis withdrawal are warranted.